Analisis Pelatihan dan Disiplin Kerja Terhadap Kinerja Karyawan Badan Penghubung Provinsi Kalimantan Timur - Pribadi, Gilang; Elmira Siska; Purwatiningsih (ARBITRASE: Journal of Economics and Accounting, 2024)
The East Kalimantan Provincial Liaison Agency in Jakarta still faces problems in terms of employee discipline. Although a number of job trainings have been conducted, Even though a number of job trainings have been carried out, improvements in measuring employee performance based on the 2022 performance report have not been fully achieved.This research aims to determine the effect of work training and work discipline partially or simultaneously on employee performance.The research method used is a quantitative method with a sampling technique using an online questionnaire which is measured using a Likert scale with a total of 55 respondents.Distribution of questionnaires was carried out in October – November 2023. Data processing was carried out with the help of SPSS software.The research results show that based on the t test, partially job training (X1) has a positive and significant effect on employee performance (Y) with a calculated t value of 7.599 > t table is 2.007 and a significance value of 0.000 < 0.05.Work discipline (X2) partially has a positive and significant effect on employee performance (Y) based on the t test with a calculated t value of 3.776 > t table is 2.007 and a significance value of 0.000 < 0.05.Based on the F test, work training (X1) and work discipline (X2) simultaneously have a positive and significant effect on employee performance (Y) with a calculated F value of 43.399 > Ftable is 3.171 and a significance value of 0.000 < 0.05.